Combination of searches for WW, WZ, and ZZ resonances in pp collisions at √s = 8 TeV with the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Davygora, Yuriy; Djuvsland, Julia Isabell; Dunford, Monica; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; Jongmanns, Jan; et al. (Physics letters, 2016)
The ATLAS experiment at the CERN Large Hadron Collider has performed searches for new, heavy bosons decaying to WW, WZ and ZZ final states in multiple decay channels using 20.3 fb−1 of pp collision data at s=8 TeV. In the current study, the results of these searches are combined to provide a more stringent test of models predicting heavy resonances with couplings to vector bosons. Direct searches for a charged diboson resonance decaying to WZ in the ℓνℓ′ℓ′ (ℓ=μ,e), ℓℓqq¯, ℓνqq¯ and fully hadronic final states are combined and upper limits on the rate of production times branching ratio to the WZ bosons are compared with predictions of an extended gauge model with a heavy W′ boson. In addition, direct searches for a neutral diboson resonance decaying to WW and ZZ in the ℓℓqq¯, ℓνqq¯, and fully hadronic final states are combined and upper limits on the rate of production times branching ratio to the WW and ZZ bosons are compared with predictions for a heavy, spin-2 graviton in an extended Randall-Sundrum model where the Standard Model fields are allowed to propagate in the bulk of the extra dimension.